Parables on a Roman Comic Stage : Together with the Commentary of Alexius Vanegas of Toledo (1542) - Nodes, Daniel Joseph (Drama and Theatre in Early Modern Europe Ser, 2017)
"âContents" -- "âAcknowledgements" -- "âAbbreviations" -- "âList of Illustrations" -- "âIntroduction. Plautine Piety and Monastic Wit in the Samarites Comoedia of Petrus Papeus (1539)" -- "âPetrus Papeus" -- "âThe Argumentum or Plot of Samarites Comoedia" -- "âThe Samaritan Story and Its Exegetical Tradition" -- "âThe Patristic Basis" -- "âThe Medieval Legacy" -- "âLiterary Hybrids" -- "âThe Fusion of Parables" -- "âMedieval Compendiums" -- "âApplying Elements from the Roman Comedies to the Bible under the New Humanism" -- "âAssessment of the Resulting Compositions" -- "âPredecessors of Papeus" -- "âContemporaries of Papeus and the Exegetical Tradition" -- "âPapeusâs Samarites Comoedia: The Characters" -- "âPapeusâs Special Handling of the Subject Matter" -- "âThe Commentary by Alejo Vanegas" -- "âThe Early Printings" -- "âModern Edition" -- "âText and Translation" -- "âPetri Papei Samarites Comoedia de Samaritano Euangelico" -- "âEpistola nuncupatoria" -- "âDramatis Personae" -- "âArgumentum" -- "âPrologus" -- "âActus primi scaena prima" -- "âActus primi scaena secunda" -- "âActus primi scaena tertia" -- "âActus primi scaena quarta" -- "âActus secundi scaena prima" -- "âActus secundi scaena secunda" -- "âActus secundi scaena tertia" -- "âActus secundi scaena quarta" -- "âActus tertii scaena prima" -- "âActus tertii scaena secunda" -- "âActus tertii scaena tertia" -- "âActus tertii scaena quarta" -- "âActus tertii scaena quinta" -- "âActus quarti scaena prima" -- "âActus quarti scaena secunda" -- "âActus quarti scaena tertia" -- "âActus quarti scaena quarta" -- "âActus quinti scaena prima" -- "âActus quinti scaena secunda" -- "âActus quinti scaena tertia" -- "âActus quinti scaena quarta" -- "âActus quinti scaena quinta".